2020
DOI: 10.1111/jep.13518
|View full text |Cite
|
Sign up to set email alerts
|

Individual and organizational factors associated with evidence‐based practice among physical and occupational therapy recent graduates: A cross‐sectional national study

Abstract: Background Occupational therapy (OT) and physical therapy (PT) programs in Canada have moved to graduate‐level entry education to address graduates' readiness for evidence‐based practice (EBP). Whether rehabilitation professionals with advanced training in EBP are meeting their responsibilities as evidence‐based professionals upon entry into practice and the factors that influence the use of evidence is unclear. The aim of this study was to examine the individual and organizational factors associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…This is somewhat concerning when studies show that early career practitioners generally hold positive attitudes towards EBP [14,16,17], but that only half use EBP [13]. Findings from our nationwide study showed that two-thirds of the participating OT and PT graduates reported using EBP upon entry to practice [5]. In studies including different health professions, PTs showed more positive attitudes towards EBP but lesser use of EBP than other professions such as physicians, nurses, podiatry and radiology [18,19].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…This is somewhat concerning when studies show that early career practitioners generally hold positive attitudes towards EBP [14,16,17], but that only half use EBP [13]. Findings from our nationwide study showed that two-thirds of the participating OT and PT graduates reported using EBP upon entry to practice [5]. In studies including different health professions, PTs showed more positive attitudes towards EBP but lesser use of EBP than other professions such as physicians, nurses, podiatry and radiology [18,19].…”
Section: Introductionmentioning
confidence: 78%
“…Enactment of EBP in the clinical and/or practice context can be operationalized through the self-reported use of EBP and indirectly through the number and type of evidence-based (EB) activities done in daily practice [5]. In our previous work, use of EBP was defined as "the actual application of EBP concepts, tools, and procedures into specific actions" [5] (p.3) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic programs play a vital role in helping shape future health providers' EBP competencies; they must first lay the foundations of EBP (the "what", "why", "how" and "when" of EBP) and, over the course of training, ensure that students move along a trajectory of progressive development of EBP competencies [40,42]. Importantly, educational institutions are expected to adequately prepare future graduates to appreciate and navigate the many organizational factors (e.g., patient overload, staff shortage) that can often impede the sustained use of EBPs [43]. In the context of becoming evidence-based practitioners, Singer and Bossarte (2006) suggest three reasons for why students may be interested in taking part in a research project during their formal training: 1) altruistic purposes" as people want to help others; 2) project-related purposes" (e.g., interesting topic); and 3) "self-serving purposes" (e.g., incentives) [44].…”
Section: Introductionmentioning
confidence: 99%